2019
DOI: 10.1017/s002966511900048x
|View full text |Cite
|
Sign up to set email alerts
|

Role of metabolomics in identification of biomarkers related to food intake

Abstract: 24Dietary assessment methods including food-frequency questionnaires and food diaries are 25 associated with many measurement errors including energy under-reporting and incorrect 26 estimation of portion sizes. Such errors can lead to inconsistent results especially when 27 investigating the relationship between food intake and disease causation. To improve the 28 classification of a person's dietary intake and therefore clarify proposed links between diet 29 and disease, reliable and accurate dietary assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Previous studies assessing the metabolic response of the body to diet have largely focused on specific foods groups, 6 yet humans eat a combination of foods that may have additive or interactive effects on human physiology. In our study, we assessed two diet quality indices to better describe the complexity of overall diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies assessing the metabolic response of the body to diet have largely focused on specific foods groups, 6 yet humans eat a combination of foods that may have additive or interactive effects on human physiology. In our study, we assessed two diet quality indices to better describe the complexity of overall diet.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary metabolic phenotypes carry rich information on environmental, lifestyle and nutritional exposures, physiological and metabolic status, and disease risks on an individual and population level. [5][6][7] Urine specimens have high concentrations of food-derived metabolites and studies have shown that urinary metabolic profiles could provide an objective measure of dietary intake. 8 Previous research identifying diet-related metabolic profiles, has largely focused on selected food groups including fruits, vegetables, meat and seafood, 5,[9][10][11][12] while dietary patterns and food processing are far less studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomics strategies, both targeted and untargeted, have clearly contributed to biomarker discovery of the last years and many reports provide the proof-of-principle of metabolomics being a key tool for nutrition research [30,213,214]. The comprehensive metabolite profiles (metabolome) can provide an overview of the metabolism with a level of description that transcends genetic information and more closely reflects the ultimate phenotype, thus helping to connect genotype to phenotype at the molecular level [210].…”
Section: Nutrigenomic Approach In the Identification Of Biomarkersmentioning
confidence: 99%
“…Aside from specific compounds, in metabolomics the analytical platform used as well as the targeted or untargeted approaches, may have a role to play in identifying metabolites [ 31 ], each of these having a number of advantages and disadvantages [ 31 ]. Food is usually a complex and diverse mixture of components that could present a metabolic potential or not.…”
Section: Introductionmentioning
confidence: 99%